First local results of the Finnish FIT-based colorectal cancer screening program - high yield, low complications - Relander, Pyry (My University, 2024)
Background: The aim of screening for colorectal cancer (CRC) is to find the cancer in its early stages, thereby improving the prognosis of cancer patients by preventing cancer-related deaths. In Finland, the CRC screening was initiated in 2022, with fecal immunochemical test (FIT) being the first-line screening method. The FIT-threshold used was 25 µg/g of hemoglobin. The aim of this retrospective study was to evaluate the results of the first screening round that was implemented by the wellbeing services county of Southwest Finland. Materials and methods: Health records of individuals aged 6070 years were scrutinized retrospectively. Participants were screened for CRC between March 1st, 2022 and April 14th, 2023. Results: Out of 36 397 FIT-invitees 23 388 (64%) returned a FIT-sample. 1407 subjects gave a FIT-positive stool sample of which 1118 (79%) took part in CRC-screening colonoscopy. A total of 63 (6%) CRCs were found. 31 CRCs (49%) were classified as early stage I tumors, 12 (19%) of which were solely suitable for endoscopic treatment. Benign, endoscopically removable polyps were detected in 889 (80%) of the colonoscopies, which resulted in a recommendation of a 3-year follow-up colonoscopy for 427 (38%) cases. There were 3 (0.27%) acute polypectomy related complications and 5 (0.45%) late post-colonoscopy complications. Conclusions: This is the first study to show the prevalence of CRC amongst participants of the newly implemented Finnish national CRC-screening program. Nearly half the patients with CRC were diagnosed in the early stage, and the polyp detection rate was 80%. Complications were uncommon.